Communication and collaboration competence within the digital competence framework: a bibliometric analysis - Hong Hue Cao; Lai Thai Dao; Trung Tran; Huyen Thi Thanh Nguyen (Institute of Advanced Engineering and Science, 2025)
This paper evaluates the development of research on communication and collaboration competence within the digital competence framework (CCC-DCF), an increasingly vital area in the digital era. Bibliometric techniques were applied to analyze 449 articles published in the Scopus database from 2000 to 2023. Using VOSviewer and Biblioshiny, publication trends were tracked, leading journals and high-productivity countries identified, as well as collaboration networks, prominent scholars, most-cited documents, and frequently used keywords. Our analysis revealed a steady increase in publications over the past 23 years, with a notable surge in the last 3 years due to the fourth industrial revolution and the COVID-19 pandemic. MDPI AG was the leading publisher, with the United States and Spain as the top-producing countries. Diana Andone and Mark Frydenberg were the most prolific authors, and the British Journal of Educational Technology was the most cited journal. The study also explored collaborations among authors and countries through visualization analysis. Key frequently appearing terms included digital competences, higher education, information and communication technologies, and collaborative learning. This research forms a basis for future studies to enhance communication and collaboration competence in the digital environment for students. It also provides policymakers and researchers with key authors and impactful studies for further exploration.